Analysis levelized cost of energy from the perspective of an power purchase agreements for airborne wind power technology - Mendonça, Anny Key de Souza; Bornia, Antonio Cezar (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
With the need to diversify the national electric matrix to expand the generation capacity, the searches for new technologies capable of contributing to supply the national demand are fundamental. In this sense, the development of wind energy technology, but specifically high-altitude wind energy using wired airfoils, is an attractive possibility, given the high national wind potential. This research aimed to analyze the cost models used in the literature to assess the leveled cost of energy (LCOE) from the perspective of an power purchase agreements (PPAs) and to simulate the leveled cost of energy for a wind farm with the innovative technology of wired airfoils. For this, we chose two cities Fortaleza (CE) and Florianópolis (SC) to carry out the simulations. The wind farms are identical, with the same number of wind turbines, the parameters that have been modified are, the amount of energy supplied by each of the scenarios, to visualize the influence of the capacity factor of each scenario within the real and nominal LCOE and the PPA real and nominal after 20 years of analysis. As wind energy is not a constant source of supply, the simulation considered the limits of energy delivery that are above or below the minimum limit of energy delivery. The results demonstrated economic viability in almost all scenarios, with greater attractiveness for scenarios with an increase in the capacity factor. When financial parameters such as federal and state charges are varied downwards, all scenarios investigated are attractive to development with an IRR greater than the reference value.